Does Humanity Matter? Analyzing the Importance of Social Cues and Perceived Agency of a Computer System for the Emergence of Social Reactions during Human-Computer Interaction. (5th August 2012) - Appel, Jana; von der Pütten, Astrid; Krämer, Nicole C.; Gratch, Jonathan
Abstract : Empirical studies have repeatedly shown that autonomous artificial entities elicit social behavior on the part of the human interlocutor. Various theoretical approaches have tried to explain this phenomenon. The agency assumption states that the social influence of human interaction partners (represented by avatars) will always be higher than the influence of artificial entities (represented by embodied conversational agents). Conversely, the Ethopoeia concept predicts that automatic social reactions are triggered by situations as soon as they include social cues. Both theories have been challenged in a 2 × 2 between subjects design with two levels of agency ( low: agent, high: avatar ) and two interfaces with different degrees of social cues ( low: textchat, high: virtual human ). The results show that participants in the virtual human condition reported a stronger sense of mutual awareness, imputed more positive characteristics, and allocated more attention to the virtual human than participants in the text chat conditions. Only one result supports the agency assumption; participants who believed to interact with a human reported a stronger feeling of social presence than participants who believed to interact with an artificial entity. It is discussed to what extent these results support the social cue assumption made in the Ethopoeia approach.